Reactive oxygen species are messengers in maintenance of human and guinea pig gallbladder tonic contraction - Cong, Ping; Xiao, Zuo-Liang; Biancani, Piero; Behar, Jose (American journal of physiology: Gastrointestinal and liver physiology, 2007)
The tonic contraction of human and guinea pig gallbladder (GB) is dependent on basal levels of PGE 2 and thromboxane A 2 (TxA 2 ). The pathway involved in the genesis of these prostaglandins has not been elucidated. We aimed to examine the source of reactive oxygen species (ROS) and whether they contribute to the genesis of GB tonic contraction by generating basal prostaglandin levels. Tonic contraction was studied in human and guinea pig GB muscle strips treated with ROS scavengers (Tiron and catalase), apocynin (an inhibitor of NADPH oxidase), and NOX-1 small interference RNA (siRNA). The subunits of NADPH oxidase and their functional roles were determined with specific antibodies in GB muscle cells. ROS scavengers reduced the GB tonic contraction and H 2 O 2 and PGE 2 levels. Apocynin also inhibited the tonic contraction. Antibodies against subunits of NADPH oxidase present in GB muscle cells lowered H 2 O 2 and PGE 2 levels. NOX-1 siRNA transfection reduced the tonic contraction, NOX-1 expression, and levels of H 2 O 2 and PGE 2 . Tiron and apocynin inhibited the expected increase in tension and H 2 O 2 levels induced by stretching of muscle strips. H 2 O 2 increased the levels of PGE 2 and TxA 2 by increasing platelet-activating factor-like lipids that phosphorylate p38 and cPLA 2 sequentially. H 2 O 2 generated by NADPH oxidase participates in a signal transduction pathway that maintains the GB tonic contraction by activating PAF, p38, and cPLA 2 to generate prostaglandins.